Cost-effectiveness Analysis of Radium-223 Dichloride in Metastatic Castration-Resistant Prostate Cancer Patients Without Previous Chemotherapy Treatment in Spain - Eva Tirado Mercier; Daniel Callejo Velasco; Marta Rubio Cabezas; Cristina Moretones Agut; Meritxell Granell Villalón (Journal of Health Economics and Outcomes Research)
**Purpose:** To perform a cost-effectiveness analysis of radium-223 plus Best Supportive Care (BSC) compared to BSC in the treatment of patients with metastatic castration-resistant prostate cancer (mCRPC) and without previous docetaxel treatment in Spain.